2015
DOI: 10.1093/nar/gkv246
|View full text |Cite
|
Sign up to set email alerts
|

The chromatin scaffold protein SAFB1 localizes SUMO-1 to the promoters of ribosomal protein genes to facilitate transcription initiation and splicing

Abstract: Early steps of gene expression are a composite of promoter recognition, promoter activation, RNA synthesis and RNA processing, and it is known that SUMOylation, a post-translational modification, is involved in transcription regulation. We previously found that SUMO-1 marks chromatin at the proximal promoter regions of some of the most active housekeeping genes during interphase in human cells, but the SUMOylated targets on the chromatin remained unclear. In this study, we found that SUMO-1 marks the promoters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 31 publications
(55 reference statements)
0
37
0
1
Order By: Relevance
“…In contrast, in response to serum stimulation, unmethylated PRC2 binds MALAT1 and localises to interchromatin granules where gene expression is activated. Another important instance of positive regulation of gene expression has been identified by Liu et al [38]. SAFB was shown to recruit SUMO-1 to gene promoters, where the sumoylated SAFB enhanced RNAPolII activity at ribosomal protein genes as well as subsequent processing of mRNA.…”
Section: Transcriptionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, in response to serum stimulation, unmethylated PRC2 binds MALAT1 and localises to interchromatin granules where gene expression is activated. Another important instance of positive regulation of gene expression has been identified by Liu et al [38]. SAFB was shown to recruit SUMO-1 to gene promoters, where the sumoylated SAFB enhanced RNAPolII activity at ribosomal protein genes as well as subsequent processing of mRNA.…”
Section: Transcriptionmentioning
confidence: 96%
“…Golebiowski et al [36] reported sumoylation of SAFB1 linked to the stress response, whereas Garee et al [37] provided evidence for sumoylation being involved in the repression of transcription by SAFB1. Most recently, SUMOylated SAFB was shown to enhance transcription of ribosomal promoter genes [38].…”
Section: Post-translational Modificationmentioning
confidence: 99%
“…More recently, purification of chromatin-associated proteins sumoylated by SUMO-1 confirmed sumoylation of several splicing factors, such as hnRNP A1, SF3A2 and SNRNP200, during S phase of the cell cycle (Liu et al 2015). In the same study, Scaffold Associated Factor-B (SAFB), known to interact with the CTD of RNAPII, was shown to be a SUMO-1 substrate that binds promoters of highly expressed genes.…”
Section: 4 Splicingmentioning
confidence: 94%
“…Studies describing sumoylation of RNA binding proteins and factors involved in 3′ pre-mRNA processing, transcription termination, RNA editing and mRNA export (Vassileva and Matunis 2004; Desterro et al 2005; Vethantham et al 2008, 2007; Xu et al 2007; Lamoliatte et al 2014; Richard et al 2013) have helped to expand the role of this modifier to the field of RNA processing and metabolism (reviewed in Rouviere et al 2013). Developing large scale mass spectrometry (MS)-based proteomics and affinity purification strategies using for example tagged SUMO peptides, several groups have identified a number of proteins involved in RNA processing events such as capping, splicing, polyadenylation and mRNA export in yeast (Panse et al 2004; Wohlschlegel et al 2004; Wykoff and O'Shea 2005; Hannich et al 2005; Denison et al 2005), mammals (Zhao et al 2004; Vertegaal et al 2004, 2006; Li et al 2004; Manza et al 2004; Rosas-Acosta et al 2005; Gocke et al 2005; Guo et al 2005; Golebiowski et al 2009; Becker et al 2013; Lamoliatte et al 2014; Liu et al 2015; Bruderer et al 2011; Hendriks et al 2014; Matic et al 2010; Tammsalu et al 2014; Schimmel et al 2014; Blomster et al 2009; Tatham et al 2011), flies (Nie et al 2009), worms (Kaminsky et al 2009) and plants (Miller et al 2010). In one of these studies, a significant proportion (17%) of the SUMO-modified proteins identified were found to be involved in RNA-related processes (Denison et al 2005).…”
Section: 2 Rna Processing Factors As Sumoylation Substratesmentioning
confidence: 99%
See 1 more Smart Citation